Mengklarifikasi Istilah“Jumat Agung”Menurut Kajian Tipologi Berdasarkan Keluaran 12:1-42 - Yohanis Banamtuan (Jurnal Apokalupsis, 2022)
Easter is a very sacred holiday for Christians, but as time goes on there are other terms attached to this sacred holiday and not all of these terms give meaning to Easter, on the contrary, it has the potential to obscure its meaning. One of the terms referred to above is the term “Good Friday.” This term has been used for a long time and without realizing it has reduced and confused the true meaning of Easter so that Easter is only understood as an event of Christ's resurrection, while the event of Jesus' death is commemorated as "Good Friday." Thus, an effort is needed to clarify the concept and use of the term "Good Friday" today. The method used is the Typological method by analyzing the meaning of Easter in the text of Exodus 12:1- 42 to reveal the true meaning of Easter according to the Bible. The results of this study found that Easter should be commemorated from the event of death until the resurrection of Christ. Therefore, the meaning and celebration of Easter which is understood as an event of Christ's resurrection is a misconception and is not in accordance with the meaning of Easter as intended by the Bible. The use of the term 'Good Friday' by itself is unnecessary in today's Easter celebrations